Behavioral Health and Service Use Among Civilian Wives of Service Members and Veterans Evidence from the National Survey of Drug Use and Health - Breslau, Joshua (RAND Corporation, 2015)
In recent years, concerns have arisen regarding access to behavioral health care for service members and veterans of the U.S. military and their families, particularly for individuals covered by the U.S. Department of Defense Military Health System and the Veterans Health Administration. RAND Researchers examined utilization of behavioral health care among current or former wives of service members and veterans who are covered in those systems.